Role of the Insula and Vestibular System in Patients with Chronic Subjective Dizziness: An fMRI Study Using Sound-Evoked Vestibular Stimulation - Indovina, Iole; Riccelli, Roberta; Chiarella, Giuseppe; Petrolo, Claudio; Augimeri, Antonio; Giofrè, Laura; Lacquaniti, Francesco; Staab, Jeffrey P.; Passamonti, Luca (Frontiers in Behavioral Neuroscience, 2015)
Chronic subjective dizziness (CSD) is a common vestibular disorder characterized by persistent non-vertiginous dizziness, unsteadiness, and heightened sensitivity to motion stimuli that may last for months to years after events that cause acute vestibular symptoms or disrupt balance. CSD is not associated with abnormalities of basic vestibular or oculomotor reflexes. Rather, it is thought to arise from persistent use of high-threat postural control strategies and greater reliance on visual cues for spatial orientation (i.e., visual dependence), long after triggering events resolve. Anxiety-related personality traits confer vulnerability to CSD. Anomalous interactions between the central vestibular system and neural structures related to anxiety may sustain it. Vestibular- and anxiety-related processes overlap in the brain, particularly in the insula and hippocampus. Alterations in activity and connectivity in these brain regions in response to vestibular stimuli may be the neural basis of CSD. We examined this hypothesis by comparing brain activity from 18 patients with CSD and 18 healthy controls measured by functional magnetic resonance imaging during loud short tone bursts, which are auditory stimuli that evoke robust vestibular responses. Relative to controls, patients with CSD showed reduced activations to sound-evoked vestibular stimulation in the parieto-insular vestibular cortex (PIVC) including the posterior insula, and in the anterior insula, inferior frontal gyrus, hippocampus, and anterior cingulate cortex. Patients with CSD also showed altered connectivity between the anterior insula and PIVC, anterior insula and middle occipital cortex, hippocampus and PIVC, and anterior cingulate cortex and PIVC. We conclude that reduced activation in PIVC, hippocampus, anterior insula, inferior frontal gyrus, and anterior cingulate cortex, as well as connectivity changes among these regions, may be linked to long-term vestibular symptoms in patients with CSD. Furthermore, altered connectivity between the anterior insula and middle occipital cortex may underlie the greater reliance on visual cues for spatial orientation in CSD patients relative to controls.